DAMPAK KEGIATAN MUHADHARAH TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN AKIDAH AKHLAK DI MTS MUHAMMADIYAH KAJAI KABUPATEN PASAMAN BARAT - Novsa’ Diyah Zahara; Darul Ilmi; Jasmienti Jasmienti; Alimir Alimir (Universitas Pahlawan Tuanku Tambusai, 2022)
This research is a quantitative correlation research. This research is located at MTs Muhammadiyah Kajai. The population in this study were all students of class VIII, amounting to 72 people. This study draws samples by random sampling as many as 36 students. Class VIII A 24 people, VIII B 24 people and VIII C 24 people. The instrument used in this research is a questionnaire. Based on research using product moment correlation testing, it is obtained that r count is 0.637 which is greater than r table, both at the level of 5% and 2%. So that the hypothesis is accepted, because r count 0.637 > r table 0.329, so there is a positive impact between muhadharah activities on student learning outcomes in the subjects of aqidah morality. That the calculated r value is 0.637 and is included in the strong category in the range 0.600-0.799 with a value of 40.57%. Thus, there is a strong relationship between muhadharah activities and student learning outcomes in the moral aqidah subjects at MTs Muhammadiyah Kajai. This shows that the better and more active students are in participating in the activities. Keywords: Impact, Muhadharah Activities, Learning Outcomes, Akidah Akhlak